Umbilical hernia in a patient with liver cirrhosis - Shimamura, Yoshinosuke (J Gen Fam Med, 2020)
This manuscript presents a case report of umbilical hernia in a patient with liver cirrhosis, associated with acute kidney injury. The purpose of this article is to facilitate physicians in understanding that emergent treatment is required for the incarcerated umbilical hernia and this condition can be associated with acute kidney injury. [Image: see text]